Lower brachial artery flow-mediated dilation is associated with a worse prognosis and more lung parenchymal involvement in Covid-19: Prospective observational study. Issue 33 (19th August 2022) - Güz, Göksel; Demirgan, Serdar
Abstract : Severe acute respiratory syndrome coronavirus-2 is a highly infectious pathogenic coronavirus, which has appeared toward the end of 2019. The virus seen all over the world caused a pandemic of an acute respiratory disease named coronavirus disease 2019 (Covid-19). It has been shown that the virus that uses angiotensin-converting enzyme 2 receptors is causing endothelial dysfunction resulting in vascular inflammation and coagulopathy. It is possible to assess endothelial dysfunction by the flow-mediated dilatation (FMD) technique. Our study aimed to demonstrate the effect of endothelial dysfunction assessed using the FMD on prognosis and mortality in the patients hospitalized with the diagnosis of Covid-19. In this prospective observational study, endothelial functions of 94 patients hospitalized due to the Covid-19 in the ward or intensive care unit (ICU) were evaluated by FMD. The relationship among endothelial dysfunction and prognosis of disease, biochemical parameters, lung involvement, and mortality was investigated. We found that the FMD% values of the Covid-19 ICU patients compared to those followed up in the ward (2.66 ± 0.62 vs. 5.23 ± 1.46/ P < .001) and those who died due to Covid-19 compared to those who were discharged alive (2.57 ± 0.22 vs. 4.66 ± 1.7/ P < .001) were significantly lower. There were moderate negative correlation between FMD% and peak values of D-dimer (r = −0.52, P < .001), troponin (r = −0.45, P < .001), ferritin (r = −0.47, P < .001), lactate dehydrogenase (r = −0.49, P < .001), and white blood cells count (r = −0.23, P = .024). Lower FMD% was associated with higher lung parenchymal involvement ( P < .001). The optimum cutoff point of FMD in predicting mortality was found to be 3.135% (sensitivity: 1, selectivity: 0.70). According to our results, lower FMD% was associated with higher lung parenchyma involvement, ICU admission, and mortality rate in Covid-19 patients. The best cutoff point for predicting mortality of FMD was 3.135%. Nevertheless, largescale, multicenter studies are needed to evaluate lower FMD values as a risk factor for mortality in Covid-19.